Lymph node ratio as a predictor for minor salivary gland cancer in head and neck - Hidenori Suzuki (BMC, 2021)
Abstract Background We investigate whether pathological continuous variables of lymph nodes were related with survival results of carcinomas of minor salivary gland carcinoma in head and neck. Methods Forty-four cases with minor salivary gland carcinoma who underwent both primary resection and neck dissection were retrospectively enrolled. The pathological continuous variables were evaluated by the number of positive lymph nodes, lymph node ratio, and log odds of positive lymph nodes. Receiver operating curve analysis was used for the cut-off values of the carcinoma-specific death. Log-rank test and Cox’s proportional hazards model were used for uni−/multi-variate survival analyses adjusting for pathological stage, respectively. Results Lymph node ratio = 0.05 as well as log odds of positive lymph nodes = − 2.73 predicted the carcinoma-specific death. Both lymph node ratio and log odds of positive lymph nodes were significantly related with survival outcomes by the univariate analysis. Lymph node ratio ≥ 0.05 was associated with shorter disease-specific (hazard ratio = 7.90, 95% confidence interval = 1.54–57.1), disease-free (hazard ratio = 4.15, 95% confidence interval = 1.48–11.2) and overall (hazard ratio = 4.84, 95% confidence interval = 1.05–24.8) survival in the multivariate analysis. Conclusion A higher lymph node ratio of minor salivary gland carcinoma is a predictor of shorter survival results.